Bivalirudin in percutaneous coronary intervention for chronic total occlusion: A single‐center pilot study. Issue 4 (2nd August 2017) - Li, Chenguang; Xu, Rende; Shen, Yi; Dai, Yuxiang; Zhang, Feng; Ma, Jianying; Ge, Lei; Qian, Juying; Ge, Junbo
Abstract: Background: Bivalirudin has been reported to be an alternative to unfractionated heparin (UFH) for anticoagulation during percutaneous coronary intervention (PCI) and associated with less bleeding risk. However, the feasibility of bivalirudin during PCI of chronic total occlusion lesions (CTO) remains unknown. Objective: To evaluate the efficacy and safety of bivalirudin versus UFH in CTO PCI. Methods: In this prospective and randomized controlled trial in single center, CTO patients with high bleeding risk were randomized to treatment with bivalirudin (bolus 0.75 mg/kg followed by infusion of 1.75, extra bolus 0.3 mg/kg before stenting) or UFH (100 IU/kg). The primary efficacy end point was the incidence of major adverse cardiac events (MACEs, composite of all‐cause mortality, cardiac death, stent thrombosis, periprocedural myocardial infarction, or additional unplanned target lesion revascularization, or any other post‐PCI ischemic event) in‐hospital, and at 1‐year follow‐up. The primary safety end point was the occurrence of any bleeding or entry‐site complications after PCI. Results: A total of 84 high bleeding risk patients undergoing PCI for CTO lesions were enrolled. The baseline characteristics were similar in both treatment arms. In hospital MACEs rates were 21.4% in the bivalirudin group and 14.3% in the UFH group ( P = 0.393). During 1‐year's follow‐up, end points did not significantly differ between the groups either. Occurrence of the major bleeding events were 4.8% in the bivalirudin group and 9.5% in the UFH group ( P = 0.676). No entry‐site complication was observed. Conclusion: In CTO patients at high risk for bleeding undergoing PCI, our data indicates that bivalirudin appears to be at least comparable in efficacy and safety to UFH. A larger clinical trial should be designed to further elucidate its efficacy and safety.